ECMO—Challenges, strategies, and preparation from Spain. Issue 5 (26th August 2020) - Pérez de la Sota, Enrique; Eixerés‐Esteve, Andrea
Abstract: Providing complex therapies such as extracorporeal membrane oxygenation (ECMO) during outbreaks of infectious diseases has singular challenges. The impact of the SARS‐CoV‐2 pandemic has implied a mentality change by force of circumstances, and cardiac surgery has not been stranger to this trend. The need to treat critically ill patients with an unknown evolution has compelled cardiovascular surgeons to decide whether or not to implant an ECMO system, despite the limited scientific evidence available in the context of COVID‐19. To add some confusion, doubts were raised about its potential deleterious outcome in COVID‐19 patients, due to its effect on lymphocyte counts and interleukin‐6 concentrations. The care of the critically ill patient in a moment of national emergency in Spain took precedence over those possible formal doubts. The Spanish perspective on ventricular assist devices during and after the COVID‐19 pandemic, focused on ECMO as a particular case of mechanical circulatory support, is presented. We address both the challenges posed by the pandemic and the organizational model established in Spain; changes in ECMO therapy and some lessons learned for the next outbreaks are also described. It is not about reinventing the wheel in each country; it is enough to learn from experience and take advantage of the knowledge generated by those who have already gone through similar situations in our environment.